Soil mapping and process modeling for sustainable land use management - Pereira, Paulo Alexandre da Silva; Brevik, Eric C.; Muñoz-Rojas, Miriam; Miller, Bradley A. (Elsevier, 2017)
Soil Mapping and Process Modeling for Sustainable Land Use Management is the first reference to address the use of soil mapping and modeling for sustainability from both a theoretical and practical perspective. The use of more powerful statistical techniques are increasing the accuracy of maps and reducing error estimation, and this text provides the information necessary to utilize the latest techniques, as well as their importance for land use planning. Providing practical examples to help illustrate the application of soil process modeling and maps, this reference is an essential tool for professionals and students in soil science and land management who want to bridge the gap between soil modeling and sustainable land use planning.--Provided by publisher.